Pengaruh Suku Bunga, Inflasi, dan Likuiditas Perbankan terhadap Nilai Tukar Rupiah terhadap Euro - Nazhira Marsha Auni; Melsen Ramadhani; Sa'diah Maulidina Putri (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2025)
This study aims to analyze the influence of interest rates, inflation, and banking liquidity on the Indonesian rupiah exchange rate against the euro. Exchange rate movements are often driven by monetary policy dynamics, price levels, and liquidity conditions within the financial system. The research utilizes 80 monthly time-series observations consisting of the BI interest rate, inflation, M2 liquidity, and the EUR/IDR exchange rate. The analytical method employed is multiple linear regression along with classical assumption tests to ensure model validity. The results indicate that the three macroeconomic variables significantly affect the rupiah exchange rate, highlighting their importance in assessing exchange rate stability. These findings provide relevant implications for policymakers in managing monetary and banking stability in Indonesia.